2005
DOI: 10.1007/s00299-005-0938-8
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of Phalaenopsis by targeting protocorms at an early stage after germination

Abstract: A transformation procedure for phalaenopsis orchid established by using immature protocorms for Agrobacterium infection was aimed at the introduction of target genes into individuals with divergent genetic backgrounds. Protocorms obtained after 21 days of culture on liquid New Dogashima medium were inoculated with Agrobacterium strain EHA101(pIG121Hm) harboring both beta-glucuronidase (GUS) and hygromycin resistance genes. Subculture of the protocorms on acetosyringone-containing medium 2 days before Agrobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 21 publications
4
49
2
4
Order By: Relevance
“…A reproducible methodology for the genetic transformation of orchids, and better recognition of the factors affecting the transformation process, are needed in order to support this objective. Previous studies have reported orchid transformation either directly through the delivery of marker genes such as those encoding Escherichia coli β-glucuronidase (GUS) and Aequorea victoria green fluorescent protein (GFP) into plant cells by particle bombardment (Anzai et al, 1996), or indirectly through the use of A. tumefaciens (Belarmino and Mii, 2000;Chia et al, 1994;Mishiba et al, 2005;Chan et al, 2005;. Recently, we developed a convenient method for genetic modification of Phalaenopsis amabilis orchids using A. tumefaciens (Semiarti et al, 2007) in which intact protocorms (young orchid seedlings) were used for transformation.…”
Section: Transformation Of Phalaenopsis Amabilis (L) Blumementioning
confidence: 99%
“…A reproducible methodology for the genetic transformation of orchids, and better recognition of the factors affecting the transformation process, are needed in order to support this objective. Previous studies have reported orchid transformation either directly through the delivery of marker genes such as those encoding Escherichia coli β-glucuronidase (GUS) and Aequorea victoria green fluorescent protein (GFP) into plant cells by particle bombardment (Anzai et al, 1996), or indirectly through the use of A. tumefaciens (Belarmino and Mii, 2000;Chia et al, 1994;Mishiba et al, 2005;Chan et al, 2005;. Recently, we developed a convenient method for genetic modification of Phalaenopsis amabilis orchids using A. tumefaciens (Semiarti et al, 2007) in which intact protocorms (young orchid seedlings) were used for transformation.…”
Section: Transformation Of Phalaenopsis Amabilis (L) Blumementioning
confidence: 99%
“…it can easily and quickly produced in large quantities as it comes from the growth of seeds, it has a high level of regeneration, and it allows transfer of genes into protocorm (Mishiba et al, 2005).…”
Section: The Growth Of Protocorms As the Target Of Transformationmentioning
confidence: 99%
“…This compound is highly reactive towards biomolecules, which cause damage of plant tissue followed by browning and necrosis (Kuta and Tripathi, 2005). Several studies of genetic transformation using Agrobacterium with transformation targets in the form of protocorm-like bodies (plb) and orchid protocorm obtained transformation effi ciency of 4.3% in Cattleya (Zhang et al, 2010); 1.91% in Phalaenopsis hybrid (Mishiba et al, 2005); 1.7% in Phalaenopsis amabilis (Semiarti et al, 2007); and 1.3 to 2.7% in Oncidium and Odontoglossum (Raffeiner et al, 2009). To improve the transformation effi ciency, there are many studies using a variety of treatments, such as the provision of antioxidants, desiccation of transformation target before and after infection with Agrobacterium, length of co-cultivation time, density of Agrobacterium tumefaciens used in the transformation, temperature of co-cultivation process, and the addition of surfactant at the time of Agrobacterium tumefaciens infection to the explants (Opabode, 2006).…”
Section: Regeneration and Selection Of Hygromycinresistant Protocormsmentioning
confidence: 99%
See 2 more Smart Citations